2020
DOI: 10.1080/17425247.2020.1813714
|View full text |Cite
|
Sign up to set email alerts
|

Co-delivery of a RanGTP inhibitory peptide and doxorubicin using dual-loaded liposomal carriers to combat chemotherapeutic resistance in breast cancer cells

Abstract: Background: Multidrug resistance (MDR) limits the beneficial outcomes of conventional breast cancer chemotherapy. Ras-related nuclear protein (Ran-GTP) plays a key role in these resistance mechanisms, assisting cancer cells to repair damage to DNA. Herein, we investigate the co-delivery of Ran-RCC1 inhibitory peptide (RAN-IP) and doxorubicin (DOX) to breast cancer cells using liposomal nanocarriers. Research design: A liposomal delivery system, co-encapsulating DOX, and RAN-IP, was prepared using a thin-film r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…Riahi et al identified a novel mutation in RCC1 as a breast cancer susceptibility allele through exome sequencing that has exclusively been found in Tunisian breast cancer patients [ 23 ]. In fact, RCC1 blockade is being investigated as a potential therapeutic strategy against aggressive breast tumors [ 24 ]. Haggag et al showed that liposome-mediated codelivery with Ran-RCC1 inhibitory peptide could improve the antitumor effect of doxorubicin in tumor-bearing mice [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Riahi et al identified a novel mutation in RCC1 as a breast cancer susceptibility allele through exome sequencing that has exclusively been found in Tunisian breast cancer patients [ 23 ]. In fact, RCC1 blockade is being investigated as a potential therapeutic strategy against aggressive breast tumors [ 24 ]. Haggag et al showed that liposome-mediated codelivery with Ran-RCC1 inhibitory peptide could improve the antitumor effect of doxorubicin in tumor-bearing mice [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, RCC1 blockade is being investigated as a potential therapeutic strategy against aggressive breast tumors [ 24 ]. Haggag et al showed that liposome-mediated codelivery with Ran-RCC1 inhibitory peptide could improve the antitumor effect of doxorubicin in tumor-bearing mice [ 24 ]. A previous study found that downregulation of RCC1 could sensitize immunotherapy by upregulating PD-L1 via the p27kip1/CDK4 pathway in non-small cell lung cancer, and the expression of RCC1 was inversely related to the amount of immune cell infiltration [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the antitumor performance of IPLD was better than that of the combination of DOX with anti-PD-L1 antibody (αPD-L1) against subcutaneous (s.c.) CT26 tumors in BALB/c mice without apparent adverse effects. and genes, for combination administration to improve the therapeutic efficacy [58]. Therefore, liposomes play a vital role in anticancer targeted drug delivery and are of great research and clinical interest (Figure 2).…”
Section: Encapsulation Of Small Molecule Drugs With Liposomementioning
confidence: 99%
“…This kind of liposome can respond to specific stimuli, either external stimuli such as light, temperature, ultrasound and magnetism, or internal stimuli such as pH, enzyme and redox [ 56 , 57 ]. Additionally, liposomes can co-load multiple drugs with different structures, ranging from small molecules to macromolecules such as proteins and genes, for combination administration to improve the therapeutic efficacy [ 58 ]. Therefore, liposomes play a vital role in anticancer targeted drug delivery and are of great research and clinical interest ( Figure 2 ).…”
Section: Liposomementioning
confidence: 99%
“…Co-administration of RAN-IP was used to improve the sensitivity of DOX within breast cancer cell lines. 15 The use of RNA interference (RNAi) technology used to reverse multidrug resistance is a powerful treatment for reducing MDR gene expression. 16,17 siMDR1 can be combined with protease to form the RNA-induced silencing complex (RISC).…”
Section: Introductionmentioning
confidence: 99%